Effect of emotional freedom techniques on anxiety, depression and insomnia among COVID-19 patients - Marcelina Boru Tambunan; Linda Suwarni; Selviana Selviana (International Journal of Public Health Science (IJPHS), 2023)
The COVID-19 pandemic has had a massive impact on various aspects, including mental health, especially for people confirmed positive for COVID-19. People who are positively confirmed for COVID-19 tend to experience decreased immunity caused by feelings of anxiety, depression, and insomnia. emotional freedom technology (EFT) therapy has been proven to reduce mental health disorders but has never been applied to people who are positively confirmed for COVID-19. This study aimed to examine the effect of EFT therapy on mental health disorders (anxiety, depression, and insomnia) in COVID-19 patients in Pontianak City. This research method is quantitative with a quasi-experimental design in the COVID-19 isolation area provided by the Pontianak City government, namely Upelkes and Rusunawa in June 2021. The total sampling was employed consisting of 42 people. A validated questionnaire on anxiety, depression, and insomnia was employed as a research instrument. A repeated ANOVA test was used to analyze research data. The results showed that EFT therapy was effective in reducing anxiety, depression, and insomnia scores in positively confirmed people for COVID-19 (p-value <0.05). EFT therapy can overcome mental health disorders experienced by people who are positively confirmed for COVID-19 and as an alternative therapy to speed up the healing process.